2020
DOI: 10.1007/s10342-020-01325-0
|View full text |Cite
|
Sign up to set email alerts
|

The Dinaric Mountains versus the Western Carpathians: Is structural heterogeneity similar in close-to-primeval Abies–Picea–Fagus forests?

Abstract: In this study, we analysed patterns of spatial variation in the basal area of live and dead trees and structural complexity in close-to-primeval forests in the Dinaric Mts. The results were compared with an analogous study conducted in the Western Carpathians. The research was carried out in the Janj, Lom and Perucića forest reserves (Bosnia and Herzegovina) in mixed-species stands of silver fir Abies alba Mill., European beech Fagus sylvatica L. and Norway spruce Picea abies (L.) H. Karst. In the core zones o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 64 publications
3
10
0
1
Order By: Relevance
“…strongly depend on the window size and kernel used in the smoothing procedure and that results obtained using different settings of these parameters should not be compared. The results resemble former findings indicating that phase classification outputs depend on the spatial scale being considered [23,68,69] and that rapidly increasing proportions and average patch sizes of the stand fragments with complex dbh structures close to the overall stand-level distribution are a universal feature of multiaged forests with strongly randomized patterns of structural heterogeneity [18,35,43,56,[70][71][72].…”
Section: Limitations Of Using Moving Windows With Overlap For Patch C...supporting
confidence: 81%
See 4 more Smart Citations
“…strongly depend on the window size and kernel used in the smoothing procedure and that results obtained using different settings of these parameters should not be compared. The results resemble former findings indicating that phase classification outputs depend on the spatial scale being considered [23,68,69] and that rapidly increasing proportions and average patch sizes of the stand fragments with complex dbh structures close to the overall stand-level distribution are a universal feature of multiaged forests with strongly randomized patterns of structural heterogeneity [18,35,43,56,[70][71][72].…”
Section: Limitations Of Using Moving Windows With Overlap For Patch C...supporting
confidence: 81%
“…This conclusion well corresponds with research suggesting that structural heterogeneity occurs primarily in small areas and diminishes rapidly with increasing spatial scales [70,71,81]. Although homogeneously structured patches occur, they cover a smaller proportion of the total forest area than those that are heterogeneously structured [34,35,43,[54][55][56][57]86]. Glatthorn et al [87] concluded that forest development takes place on a continuous scale and that discrimination between development stages splits continuous datasets at selected thresholds.…”
Section: Randomness Vs Patchiness-empirical Examplessupporting
confidence: 79%
See 3 more Smart Citations